Thermo-/chemo-responsive shape memory/change effect in hydrogels and their composites - Zhang, Jiliang (2014)
Shape memory material (SMM) is a type of smart material, which after being severely and quasi-plastically deformed, is able to return its original shape at the presence of the right stimulus. This feature is known as the shape memory effect (SME). Great attention has been attracted on this feature ever since it was discovered. On the other hand, the shape change effect (SCE) is defined as the shape change in a linear or nonlinear fashion with or without hysteresis in response to the applied right stimulus. Many applications of both effects have already been in engineering practice. In this project, water/moisture-content dependent behaviors in three hydrogels are systematically investigated. It is found that at lower water/moisture contents, all hydrogels have the thermo-responsive and moisture (or water)-induced SME; while at higher water/moisture contents, the hydrogel has the rubber-like mechano-responsive SCE and water-induced SCE. Furthermore, it is shown that on the one hand, programming can be realized by means of distortion at high temperatures (above the glass transition temperature, Tg) of a hydrogel with lower water/moisture content or dehydration after pre-deforming a piece of rubber-like hydrogel (which has higher water/moisture content). Some possible applications utilizing the SME/SCE either individually or combined together are proposed. On the other hand, hydrogel can be used as the elastic matrix in a hybrid for tailored SME.